Pengaruh Pelatihan Beban Menggunakan Bench Press Terhadap Daya Ledak Otot Lengan Tim Porprov Bola Tangan Kabupaten Lamongan - Muhammad Brillian Rifti Aditia; Fatkur Rohman Kafrawi (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Handball sport is a team sport where in one team there are seven players including 6 players and one goalkeeper and has the aim of putting the ball into the opponent's goal as much as possible and is played in two categories of men and women. In the sport of handball, arm muscle explosiveness is needed when shooting and also passing. This study aims to determine the effect of load training using bench press on the explosive power of the arm muscles of handball athletes. This research is a quasi experimental study with a one group design conducted an initial test and final test (one group pretest posttest design), this study uses the VBT metric application to make it easier to analyze the training program. The subjects in this study were 14 male athletes from Lamongan Regency with age categories 16 - 23 years and body weight between 52 - 85 kg, and Body Mass Index (BMI) found 11 athletes with normal weight, 1 athlete with less weight, and 2 athletes with excess weight. The instrument used in this study was the two hand medicine ball push test. The data collected from the results of this study were analyzed using normality test, homogeneity test and hypothesis testing. The results showed the value of t count = 16.369> t table 2.160 or the significance value of ρ of 0.000 <0.05 and there is a difference in the average value of 1.2179. So the conclusion that can be drawn is that weight training using bench press can provide a significant influence on increasing the explosive power of the arm muscles.